Pex13 and Pex14, the key components of the peroxisomal docking complex, are required for peroxisome formation, host infection and pathogenicity-related morphogenesis in Magnaporthe oryzae. Issue 1 (1st January 2019) - Wang, Jiao-Yu; Li, Ling; Chai, Rong-Yao; Qiu, Hai-Ping; Zhang, Zhen; Wang, Yan-Li; Liu, Xiao-Hong; Lin, Fu-Cheng; Sun, Guo-Chang
ABSTRACT: Peroxisomes are ubiquitous organelles in eukaryotic cells that fulfill multiple important metabolisms. Pex13 and Pex14 are key components of the peroxisomal docking complex in yeasts and mammals. In the present work, we functionally characterized the homologues of Pex13 and Pex14 (Mopex13 and Mopex14) in the rice blast fungus Magnaporthe oryzae . Mopex13 and Mopex14 were peroxisomal membrane distributed and were both essential for the maintenance of Mopex14/17 on the peroxisomal membrane. Mopex13 and Mopex14 interacted with each other, and with Mopex14/17 and peroxisomal matrix protein receptors. Disruption of Mopex13 and Mopex14 resulted in a cytoplasmic distribution of peroxisomal matrix proteins and the Woronin body protein Hex1. In the ultrastructure of Δmopex13 and Δmopex14 cells, peroxisomes were detected on fewer occasions, and the Woronin bodies and related structures were dramatically affected. The Δmopex13 and Δmopex14 mutants were reduced in vegetative growth, conidial generation and mycelial melanization, in addition, Δmopex13 showed reduced conidial germination and appressorial formation and abnomal appressorial morphology. Both Δmopex13 and Δmopex14 were deficient in appressorial turgor and nonpathogenic to their hosts. The infection failures in Δmopex13 and Δmopex14 were also due to their reduced ability to degrade fatty acids and to endure reactive oxygen species and cell wall-disrupting compounds. Additionally, Mopex13 and Mopex14 were required for the sexual reproduction of the fungus. These data indicate that Mopex13 and Mopex14, as key components of the peroxisomal docking complex, are indispensable for peroxisomal biogenesis, fungal development and pathogenicity in the rice blast fungus.